Pengaruh Celebrity Endorser Dan Word Of Mouth Terhadap Minat Beli Ulang Melalui Brand Trust Pada Produk Kosmetik Focalluresebagai Variabel Moderasi - Risqy Aziz Basuki; Nanda Alika Fairuz (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2021)
This study aims to determine and explain the effect of Celebrity Endorser on Repurchase Intention, the influence of Word of Mouth on Repurchase Intention, the effect of Brand Trust on Repurchase Intention, the influence of Brand Trust as a moderating variable on Celebrity Endorser and Repurchase Intention on Focallure Account Followers in Instagram, the influence of Brand Trust as a moderating variable on Word Of Mouth and Repurchase Intention on Focallure Followers on Instagram. The method used in this study is a quantitative method. The results show that Celebrity Endorser has a positive and insignificant effect on Repurchase Intention, Word of Mouth has a positive and significant effect on Repurchase Intention, Brand Trust has a positive and significant effect on Repurchase Intention, Brand Trust can be a moderating variable of Celebrity Endorser on Repurchase Intention, Brand Trust can be a moderating variable of Word of Mouth on Repurchase Intention. Keywords: Brand Trust, Celebrity Endorser, Repurchase Intention, Word of Mouth